Airships and Conventional Air Transportation Systems. Insights and Challenges for Portugal - Lia Pereira; Jorge Silva (European Regional Science Association (ERSA), 2011)
Technological developments and environmental concerns are among several reasons that are bringing up once again the concept of new air transportation vehicles like the airships. Nowadays airships have several applications such as: heavy cargo and point-to-point transportation, advertising, observation, patrolling and monitoring, research, and tourism. This work examines the technological improvements in this particular sector of aviation and shows the feasibility of airships in certain market niches. Key-words: Airships, Cargo and Passenger Air Transportation, Market Niches
Keywords: 330